The utilisation of Asolla filiculoides Lam. as a biofertiliser under dryland conditions - Kiguli, Lillian Nakibuuka (Rhodes University, Faculty of Science, Botany Department, 2000)
The response of wheat to soil fertilised with varying quantities of the water fern Azolla filiculoides was investigated. Experiments were conducted to differentiate between the effects of increased soil mineral status and water status. In the preliminary investigation, experiments were carried out in the greenhouse using potted wheat grown in sand with varying proportions of A. filiculoides that had been subjected tovarious pre-treatments. The pre-treatments were fresh, dry and heated A. filiculoides applied at 20%, 50% and 80% volume per 3000 ml. There were significant differences in the measured growth parameters between the plants grown in the various treatments. In addition, the grain yield of wheat plants varied with the different treatments. Results of the preliminary study showed that the addition of heated and dried A. filiculoides resulted in significantly better growth than the addition of fresh A. filiculoides in sand. For fresh biomass, grain weights, Leaf area ratio (LAR) and relative growth rate (RGR), the performance of dried A. filiculoides was as good as that of the heated A. filiculoides. Productivity of wheat in the heated treatments increased significantly with increasing proportion of A. filiculoides added to sand, while in dry treatments there were no significant increases in productivity in the preliminary study. This supported the hypothesis that A. filiculoides, a notorious water weed can be put to agricultural use under dryland conditions in poor nutrient soils. Further investigations using dried A. filiculoides in sand and topsoil showed that the use of the same amounts of the dried fern made no significant short term impact on topsoil grown winter wheat but significantly improved the productivity of wheat in sand. Results showed that the addition of dried 20% Azolla to sand improved the soil fertility to levels equalling the quality of the control topsoil, but the addition of 80% Azolla to sand led to significantly greater wheat productivity than all other treatments. The addition of dried 20% Azolla (8.14 Ã— 10^3 kg ha^(-1)) in sand produced as much wheat biomass as the addition of the recommended NPK fertiliser (30 kg N ha^(-1)) to sand. A comparison between the topsoil and sand-grown plants showed differences in flowering time but these had no effect on the final grain and above ground biomass.
Keywords: Asolla as fertilizer